The Interactive Electronic Book Learning Media: Social Science Learning Motivation of Students - Utami, Rohyana Felisa; Ratnaningrum, Ika (Integrated Science Education Journal, 2025)
Purpose of the study: This study aims to develop, validate, and evaluate the effectiveness of Interactive Electronic Book Media—referred to as Bukelin—to enhance student motivation in learning IPAS (Ilmu Pengetahuan Alam dan Sosial) among fifth-grade elementary school students Methodology: The research adopts the Research and Development (R&D) approach, utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants were Grade V students of Elementary School Lemberang, Banyumas. Data collection involved a combination of instruments, including tests, interviews, observations, questionnaires, and documentation to comprehensively assess feasibility and effectiveness. Main Findings: The feasibility test results showed that the Interactive Electronic Book Media was well-received, with a 71% feasibility score from media experts (categorized as “eligible”) and a 90% score from material experts (categorized as “very feasible”). Effectiveness was measured through pretest and posttest scores, resulting in an N-gain value of 0.7096, indicating a high increase in student motivation. Students demonstrated improved engagement, enthusiasm, and autonomy during IPAS learning sessions with Bukelin. Novelty/Originality of this study: Unlike conventional printed textbooks, Bukelin integrates interactive multimedia elements, including images, audio, and video, creating a dynamic, student-centered learning experience. This digital approach not only supports independent and active learning but also aligns with current technological trends in education. The study contributes to the limited research on multimedia integration in primary school contexts in Indonesia and offers a practical solution to enhance learning motivation through interactive digital tools. These findings suggest that well-designed digital media can significantly enrich the elementary learning experience.